Self-regulation as a mediator in motor learning: The effect of the cognitive orientation to occupational performance approach on children with DCD - Sangster Jokic, C.; Polatajko, H.; Whitebread, D. (Adapted Physical Activity Quarterly, 2013)
Children with developmental coordination disorder (DCD) experience difficulty performing everyday motor tasks. It is has been suggested that children with DCD have fewer self-regulatory (SR) skills with which to acquire motor skills. This article presents the results of an exploratory study examining the development of SR competence among ten 7-9-year-old children with DCD participating in the Cognitive Orientation to daily Occupational Performance (CO-OP) program (Polatajko & Mandich, 2004). Using a quantitative observational coding method, children`s SR behavior was examined and compared across intervention sessions. Results indicate that children demonstrating improved motor performance similarly demonstrated more independent and effective SR behaviors. In contrast, children whose motor performance remained relatively stable failed to demonstrate such a change. These findings suggest that CO-OP enables SR performance among children with motor performance difficulties and, as a result, facilitates improved task performance.